ПЕРСПЕКТИВЫ СОЗДАНИЯ РЕГИОНАЛЬНОГО КЛАСТЕРА ЖИВОТНОВОДСТВА АКМОЛИНСКОЙ ОБЛАСТИ (Экономика: стратегия и практика)
The scientific article outlines the main tendencies of the economy of the agrarian sector of Kazakhstan at the pres- ent stage. It is revealed that the ongoing state reforms in the agrarian sector of the economy do not give the expected effect, agriculture is in a state of imbalance, a low level of management, there are no clear normative distributions in property relations, and financial deterioration in industries is observed. The problem of agriculture is that the products produced are not competitive in the external and internal markets, there is a high share of imports of food products.The theoretical backgrounds of cluster formation were being explored in this paper. It has been revealed that the development of clusters is a recognized tool accompanying sustainable innovative development and improving the competitiveness of agriculture in the region and the agro-industrial complex as a whole. The use of the cluster form of agricultural activity organization is provided in a number of legal and regulatory documents including some program documents of the country. The prerequisites for the cluster approach development to the functioning and progress of the national economy began to extend in the nineteenth century in the works of American scientists. M. Enright proposed the term “regional cluster” for the definition of a spatial cluster of interrelated enterprises that are similar in their specialization of companies. A regional cluster is defined as an industrial cluster where firms are members of a cluster operating in one or several related industries of the economy, and form a territorial agglomeration.The purpose of the scientific article is to reveal the economic and natural-geographical potential of the agrarian sector of the economy of the Akmola region for the creation of a cluster in livestock in this region. The analysis of the main indicators of livestock breeding in the Akmola region was carried out. Recommendations are given on the formation and development of the foundations of a regional cluster in the livestock sector in the region.